Thinking of Country House Based on the Concept of Green Development: Take Nanyang, Henan as an example. Issue 1 (May 2021) - Zhang, Yongwang; Wang, Wanjiang; Li, Chen; Liu, Mengjun; Ni, Pingan
Abstract: With the introduction of a series of policies such as rural revitalization, beautiful rural areas, and a comprehensive well-off society, the concept of green development of rural housing has attracted widespread attention. The green development of rural houses can effectively slow down the speed of global climate warming, reduce environmental pollution, reduce energy consumption of buildings and achieve sustainable development of buildings. Based on a field survey in a village in Nanyang City, this article summarizes the current problems of rural housing development, and combines current green development concepts, local lifestyles and living habits, and puts forward some practical suggestions for rural construction and development; the green of rural housing Urbanization can better promote rural construction and provide relevant references for the long-term sustainable development of rural housing in the future.